Humanization of nursing care: a systematic review - Reyes-Téllez, Ángeles; González-García, Alberto; Martín-Salvador, Adelina; Gázquez-López, María; Martínez-García, Encarnación; García-García, Inmaculada (Frontiers in Medicine, 2024)
Advances in healthcare in recent years have resulted in the automation and standardization of healthcare. Consequently, care has become dehumanized. There is a lack of trust from patients toward the health care system, as well as feelings of stress, exhaustion, and fatigue among professionals. The aim of this article is to describe the humanization actions in nursing care, as well as the barriers and facilitating strategies to carry them out. A systematic review of the scientific literature has been carried out following the recommendations of the PRISMA declaration. The search was carried out in the WOS, SCOPUS, CINAHL Complete, MEDLINE (via PubMed), EMBASE and Cochrane Library databases. The keywords used were “humanization of assistance,” “nursing care,” and “nurse–patient relations,” restricting to original studies in English or Spanish, from 2018 to 2022. One author performed the search, selection, and screening of records. Two authors were involved in data extraction, and a third author decided in case of conflict. The systematic review was guided by ethical conduct that respects authorship and reference sources. Of the 744 articles initially identified, 27 were included in this review. Methodological quality was assessed following the STROBE statement or the CASPe and MMAT tools. The main barriers were found to be the lack of training of nurses and their working conditions, as well as the unwillingness of the institutions. Facilitating strategies consisted of solving implementation problems, promoting communication to strengthen nurse–patient relationships and accompaniment by family members. The main interventions are related to the physical environment and have been studied in obstetrics and pediatrics services. Barriers related to training, work situation and lack of institutional involvement are complemented with facilitating strategies that aim to implement the humanized model at a general level.